Variations in glutamine deamidation for a Châtelperronian bone assemblage as measured by peptide mass fingerprinting of collagen. Issue 1 (1st January 2017) - Welker, Frido; Soressi, Marie A.; Roussel, Morgan; van Riemsdijk, Isolde; Hublin, Jean-Jacques; Collins, Matthew J.
Abstract: Peptide mass fingerprinting of bone collagen (ZooMS) has previously been proposed as a method to calculate the extent of the non-enzymatic degradation of glutamine into glutamic acid (deamidation). Temporal and spatial variation of glutamine deamidation at a single site, however, has not been investigated. Here we apply ZooMS screening of Châtelperronian and Early Holocene bone specimens from Quinçay, France, to explore temporal and spatial variation in glutamine deamidation. Our results indicate that chronological resolution is low, while spatial variation is high. Nevertheless, our analysis allows the identification of bone specimens that have undergone diagenetic histories remarkably different (either in length or in type) from spatially related bone specimens. Therefore, ZooMS ammonium-bicarbonate screening is capable of testing bone assemblage homogeneity, which could guide subsequent analysis and interpretation. GRAPHICAL ABSTRACT: